Reliable change in developmental outcomes of Brain Balance® participants stratified by baseline severity - Jackson, Rebecca; Jordan, Joshua T. (Frontiers in Psychology, 2023)
The effects of comprehensive multimodal programs on developmental outcomes have not been well-studied. Emerging evidence suggests a possible role for the Brain Balance® (BB) program, a multimodal training program, in serving as a nonpharmacologic approach to addressing cognitive, attentional, and emotional issues in youth. In this analysis, we examined the effects of 3 months of participation in the BB program on the outcomes of children and adolescents with developmental difficulties (N = 4,041; aged 4–18 years; 69.7% male). Parent-rated scores on the Brain Balance–Multidomain Developmental Survey (BB-MDS) were used to assess six areas at baseline and post-program: (1) negative emotionality; (2) reading/writing difficulties; (3) hyperactive/disruptive behavior; (4) academic disengagement; (5) motor/coordination problems; and (6) social communication problems. To estimate change from pre- to post-program, we calculated effect size (Cohen’s d) and the Reliable Change Index (RCI) for groups stratified by baseline severity. There was a very large effect size for the moderate/high severity (d = 1.63) and extreme severity (d = 2.08) groups, and a large effect size for the mild severity group (d = 0.87). The average percentage of participants who observed reliable change over all BB-MDS domains was 60.1% (RCICTT) for extreme severity, 46.6% (RCICTT) for moderate/high severity, and 21.1% (RCICTT) for baseline mild severity. In additional assessments of primitive reflexes and sensory motor activity, students demonstrated significantly diminished primitive reflexes from pre- to post-participation and significant improvements in sensory motor skills including fine motor skills, gait and aerobic ability, proprioception, rhythm and timing, and eye-gaze stability. Overall, these results demonstrate improvements in primitive reflex integration and sensory motor skills, as well as statistically significant reliable change in emotionality, reading/writing, behavior, academic engagement, motor skills, and social communication in BB participants from pre- to post-program, with the probability and degree of change increasing as the participants’ baseline severity increases. These results contribute to the growing literature on the need for evidence-based nonpharmacologic approaches to addressing developmental issues. Future research with well-controlled designs, longitudinal follow-up, implementation across settings, and participant groups in which diagnoses are known, will help to more fully characterize the effects of the BB program.